## 12 Reputation

14 years, 308 days

## Curly braces with \maple*...

I forgot the evalb(...) in my previous post. When the solution is a finite sequence of values: 1.) An equation with two solutions: \maple*{evalb(\{solve(24-18*exp(-2*x)+3*exp(-4*x)=0)\} = \{\$RESPONSE\})} 2.) An inequality where the solution is the union of two intervals \maple*{evalb(\{solve(1/(2*x-4) <= 1/(3*x+9))\} = \{\$RESPONSE\})}

## Curly braces with \maple*...

I forgot the evalb(...) in my previous post. When the solution is a finite sequence of values: 1.) An equation with two solutions: \maple*{evalb(\{solve(24-18*exp(-2*x)+3*exp(-4*x)=0)\} = \{\$RESPONSE\})} 2.) An inequality where the solution is the union of two intervals \maple*{evalb(\{solve(1/(2*x-4) <= 1/(3*x+9))\} = \{\$RESPONSE\})}

## Curly braces with \maple*...

When the solution is a finite sequence of values: 1.) An equation with two solutions: \maple*{\{solve(24-18*exp(-2*x)+3*exp(-4*x)=0)\} = \{\$RESPONSE\}} 2.) An inequality where the solution is the union of two intervals \maple*{\{solve(1/(2*x-4) <= 1/(3*x+9))\} = \{\$RESPONSE\}}

## Curly braces with \maple*...

When the solution is a finite sequence of values: 1.) An equation with two solutions: \maple*{\{solve(24-18*exp(-2*x)+3*exp(-4*x)=0)\} = \{\$RESPONSE\}} 2.) An inequality where the solution is the union of two intervals \maple*{\{solve(1/(2*x-4) <= 1/(3*x+9))\} = \{\$RESPONSE\}}
 Page 1 of 1
﻿